Authority to Appoint Non-Permanent Employees by Personnel Management Officers or Other Officials - Adityawarman (International Peneliti Ekonomi, Sosial dan Teknologi, 2023)
This thesis examines and describes the dynamics of the existence of Non-Permanent Employees (PTT) after the enactment of the ASN Law and PP 49 of 2018. The nomenclature of Honorary Employees or Non-Permanent Employees (PTT) is no longer recognized in the ASN Law and PP 49 of 2018. This research aims to analyze the authority of Civil Service Development Officials in the Regions or other Officials in appointing Non-Permanent Employees (PTT) and analyzing the legal implications for the appointment of Non-Permanent Employees (PTT) after the promulgation of PP 49 of 2018. In this study using normative research types, namely normative legal research (legal research). The results of the research are: First, the ASN Law only recognizes a limited nomenclature of government employees, namely PNS and PPPK, then it is emphasized in PP 49 of 2018 which prohibits PPK or other officials from appointing non-PNS and/or non-PNS employees, from the aspect the authority of the PPK or other officials does not have authority in procuring PTT within the scope of the government agency under its auspices, previously PP 49 of 2018 procuring PTT could be carried out through the discretionary authority of each PPK. Second, the legal implications that can occur are, first, for PPK or other officials who still appoint PTT after the enactment of PP 49 of 2018 as a form of defiance of clear rules governing prohibitions and orders.